2020
DOI: 10.1007/s10008-020-04843-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aryl substituted functionalized graphene sheets and their electrochemical behavior

Abstract: We report the electrochemical behavior of free-standing functionalized graphene sheet electrode in a potential window corresponding to that of high-voltage cathode of lithium-ion batteries. Electrochemical exfoliation of graphite yielded graphene oxide sheets that were subsequently heat-treated at 300°C in inert gas atmosphere. Chemical functionalization of resulting graphene sheets with C 6 H 4 CF 3 , C 6 H 4 COOH, and C 6 H 4 N(C 2 H 5 ) 2 groups was performed using diazonium chemistry. As-prepared graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The grafting of aryl diazonium salts (ADS) to a variety of surfaces, including carbon‐based materials has been extensively studied [6–12] . Leroux and Hapiot [13] reported that the grafting density of electrografted ethynyl diazonium salts on glassy carbon can be tuned by varying the size of the protecting group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grafting of aryl diazonium salts (ADS) to a variety of surfaces, including carbon‐based materials has been extensively studied [6–12] . Leroux and Hapiot [13] reported that the grafting density of electrografted ethynyl diazonium salts on glassy carbon can be tuned by varying the size of the protecting group.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The grafting of aryl diazonium salts (ADS) to a variety of surfaces, including carbon-based materials has been extensively studied. [6][7][8][9][10][11][12] Leroux and Hapiot [13] reported that the grafting density of electrografted ethynyl diazonium salts on glassy carbon can be tuned by varying the size of the protecting group. Further, they found that a trimethylsilyl (TMS) protecting group is already bulky enough to prevent multilayer formation.…”
Section: Introductionmentioning
confidence: 99%